Spike protein of SARS-CoV-2 Omicron variant: An in-silico study evaluating spike interactions and immune evasion - Jose A. Jimenez Ruiz; Cecilia Lopez Ramirez; Cecilia Lopez Ramirez; Jose Luis Lopez-Campos; Jose Luis Lopez-Campos (Frontiers in Public Health, 2022)
BackgroundThe fundamentals of the infectivity and immune evasion of the SARS-CoV-2 Omicron variant are not yet fully understood. Here, we carried out an in-silico study analyzing the spike protein, the protein electrostatic potential, and the potential immune evasion.MethodsThe analysis was based on the structure of the spike protein from two SARS-CoV-2 variants, the original Wuhan and the Botswana (Omicron). The full-length genome sequences and protein sequences were obtained from databanks. The interaction of the spike proteins with the human Angiotensin Converting Enzyme 2 (ACE2) receptor was evaluated through the open-source software. The Immune Epitope Database was used to analyze the potential immune evasion of the viruses.ResultsOur data show that the Omicron spike protein resulted in 37 amino acid changes. The physicochemical properties of the spike had changed, and the electrostatic potentials differed between both variants. This resulted in a decrease in protein interactions, which does not establish a greater interaction with the ACE2 receptor. These changes compromise key receptor-binding motif residues in the SARS-CoV-2 spike protein that interact with neutralizing antibodies and ACE2.ConclusionsThese mutations appear to confer enhanced properties of infectivity. The Omicron variant appears to be more effective at evading immune responses.